2014
DOI: 10.1021/ic501629n
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Complexes of meso-Triaryl-25-oxasmaragdyrins

Abstract: The aromatic PO2 complexes of meso-triaryl-25-oxasmaragdyrins were synthesized by treating the free base 25-oxasmaragdyrins with POCl3 in toluene/triethylamine at refluxing temperature. The complexes are stable and characterized by X-ray and different spectroscopic techniques. In these complexes, the phosphorus(V) ion was bound to two pyrrolic nitrogen atoms of the smaragdyrin macrocycle and two oxygen atoms in tetrahedral geometry. The X-ray structure revealed that the smaragdyrin macrocycle showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Long-lived charge-separated states have been obtained by am ulti-modular approach in which sequential electron transfer leadingt os patially distantc ation and anion radical ions has been the common approach. [49] Thus,s uch chelated oxasmaragdyrins provide ag reat opportunity to build donor-acceptor systems to investigatel ight-induced electronand energy-transfer events. [39][40][41][42][43][44][45][46] Some of these hetero-macrocyclic compounds are known for their strong absorption and emission, and useful redox properties, thus making them useful materials for buildingl ight-energy-harvestings ystems.…”
Section: Introductionmentioning
confidence: 99%
“…Long-lived charge-separated states have been obtained by am ulti-modular approach in which sequential electron transfer leadingt os patially distantc ation and anion radical ions has been the common approach. [49] Thus,s uch chelated oxasmaragdyrins provide ag reat opportunity to build donor-acceptor systems to investigatel ight-induced electronand energy-transfer events. [39][40][41][42][43][44][45][46] Some of these hetero-macrocyclic compounds are known for their strong absorption and emission, and useful redox properties, thus making them useful materials for buildingl ight-energy-harvestings ystems.…”
Section: Introductionmentioning
confidence: 99%
“…Upon complexation with the BF 2 or PO 2 unit, the smaragdyrin macrocycle displayed enhanced stabilityw ith significantly altered features in the absorption and emission spectra. [7,8] We also demonstratedt hat BF 2 -oxasmaragdyrins 3 can participate in energy transfer by covalently linking the BF 2 -smaragdyrin macrocycle with energy-donating fluorophores (e.g.,b oron dipyrromethenes and porphyrins). [9][10][11][12] As mentioned above,t he BF 2 /PO 2 units in both oxasmaragdyrin complexes 3 and 4 wereo nly bound to the dipyrrin moiety,b ut the tripyrrin moiety of the smaragdyrin that containst wo donor pyrrole nitrogen atoms ando ne furan oxygen atom remained uncoordinated in these molecules.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, 25‐oxasmaragdyrins have also been shown to form both metal and non‐metal complexes . In particular, we recently demonstrated that the 25‐oxasmaragdyrins form highly fluorescent complexes with BF 2 and PO 2 ( 3 and 4 , respectively; Scheme ) bound via the two pyrrole nitrogen atoms of the dipyrrin moiety of the 25‐oxasmaragdyrin macrocycle. Upon complexation with the BF 2 or PO 2 unit, the smaragdyrin macrocycle displayed enhanced stability with significantly altered features in the absorption and emission spectra .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 25-oxasmaragdyrins exhibit very interesting spectral and electrochemical properties. The electronic properties of the 25-oxasmaragdyrins can be altered significantly by complexing it with BF 2 and PO 2 moieties (Chart 1) to prepare BF 2 -25-oxasmaragdyrin 3 [5] and PO 2 -25-oxasmaragdyrin 4 [6]. The BF 2 3 and PO 2 4 complexes of 25-oxasmaragdyrins are very stable and absorb and emit in the Vis-NIR region with decent quantum yields.…”
Section: Introductionmentioning
confidence: 99%